Meta Synthesis of Community Participation Model on Trans-Papua Road Development - Zepnat Kambu; M. Yamin Jinca; M. Saleh Pallu; M. Isran Ramli (Salehan Institute of Higher Education, 2022)
The Trans Papua road infrastructure is not only for physical growth but also for social and economic improvement (social, cultural, and environmental relations). Trans Papua establishes a new economic development center that will boost the community's income but must also reduce social, cultural, and environmental issues. Increasing community and indigenous Papuan engagement reduces social disputes. Trans-development Papua raises environmental problems in addition to economic benefits. Environmental disputes are avoided by not disturbing Lorentz National Park, which has the most comprehensive biodiversity and environment in Asia and the Pacific. To achieve Indonesia's commitment to the Sustainable Development Goals, the policy model for future consequences must be examined (SDGs). This project intends to build a dispute resolution paradigm and cooperative implementation strategies for Trans Papua road development. It starts with bottom-up perception discussions, alternative possibilities, concept creation, and Trans Papua infrastructure execution plans. This initiative intends to maximize social-community capital to speed the building of functional and efficient infrastructure for the Papuan community. The predicted benefits help the government evaluate prior Trans Papua road construction plans and guide future decision-making to accelerate and reduce road conflicts. Doi: 10.28991/CEJ-2022-08-11-08 Full Text: PDF